Case report: The art of anesthesiology—Approaching a minor procedure in a child with MPI-CDG - Chang, En-Che; Chang, Yu-Hsuan; Tsai, Yu-Shiun; Hung, Yi-Li; Li, Min-Jia; Wong, Chih-Shung (Frontiers in Pharmacology, 2022)
Background: Protein glycosylation plays an important role in post-translational modification, which defines a broad spectrum of protein functions. Accordingly, infants with a congenital disorder of glycosylation (CDG) can have N-glycosylation, O-glycosylation, or combined N- and O-glycosylation defects, resulting in similar but different multisystem involvement. CDGs can present notable gastrointestinal and neurologic symptoms. Both protein-losing enteropathy and hypotonia affect the decision of using anesthetics. We reported a case of MPI-CDG with protein-losing enteropathy and muscular hypotonia that underwent different anesthesia approach strategies of vascular access. Here, we highlight why intubation with sevoflurane anesthesia and sparing use of muscle relaxants is the optimal strategy for such a condition. Case presentation: A 25-month-old girl, weighing 6.6 kg and 64 cm tall, suffered chronic diarrhea, hypoalbuminemia, and hypotonia since birth. Protein-losing enteropathy due to MPI-CDG was documented by whole-exome sequencing. She underwent three sedated surgical procedures in our hospital. The sedation was administered twice by pediatricians with oral chloral hydrate, intravenous midazolam, and ketamine, to which the patient showed moderate to late recovery from sedation and irritability the following night. The most recent one was administered by an anesthesiologist, where endotracheal intubation was performed with sevoflurane as the main anesthetic. The patient regained consciousness immediately after the operation. She had no complications after all three sedation/anesthesia interventions and was discharged 7 days later, uneventful after the third general anesthesia procedure. Conclusion: We performed safe anesthetic management in a 25-month-old girl with MPI-CDG using sevoflurane under controlled ventilation. She awoke immediately after the procedure. Due to the disease entity, we suggested bypassing the intravenous route to avoid excess volume for drug administration and that muscle relaxant may not be necessary for endotracheal intubation and patient immobilization when performing procedures under general anesthesia in CDG patients.